Melawan Lupa: Kapitalisme Agraria dan Perlawanan Rakyat Lambu–Sape (Refleksi Gerakan Anti-Tambang di Sumbawa): Penelitian - Imran Siswadi; Imam Yuliadi (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This article examines the Lambu–Sape mining tragedy (2010–2012) as a comparative case study to explore the dynamics of agrarian capitalism and grassroots resistance to mining expansion in Sumbawa, West Nusa Tenggara. The tragedy involved the killing of civilians during protests against the exploration project by PT Sumber Mineral Nusantara (SMN), as well as the burning of a local government office. Using a qualitative, reflective case study approach, the article critically analyzes the relationship between local power, corporations, and the state in legitimizing natural resource exploitation that disregards community rights. Data were drawn from field notes, the author’s narrative reflections, civil society reports, and media documentation. The analysis employs historical-critical methods and theories from David Harvey (accumulation by dispossession), Paul Connerton (social memory), and Achille Mbembe (biopolitics). Findings reveal that the Lambu–Sape resistance reflects opposition to extractive capitalism and political conflict management. Although the mining permit was revoked, social trauma persists. The memory of the tragedy is at risk of being forgotten, underscoring the need for critical education, movement documentation, and activist regeneration. The article concludes that resisting forgetfulness is not only a moral act, but a political strategy for communities to defend their living spaces.